La dimensione costituzionale dell’emergenza: come l’epidemia moltiplica le disuguaglianze (BioLaw Journal - Rivista di BioDiritto, 2020)
The Coronavirus pandemic in spreading worldwide with important effects on the fundamental rights of everyone. The author’s argues that a compression of fundamental rights can be constitutionally justified under specific conditions, however there is a need to consider and address how these measures impact on the situation of people who already face structural discriminations, such as people deprived of personal freedom, people with disability, women and others.
Keywords: CoViD-19; pandemic emergency; inequalities; gender-based violence; disability